Compressive strength of normal strength concrete (NSC) using British standard, euro code and non-destructive test approaches - Tang, Jian An (2010)
Concrete is a very important material and widely used in construction industry. It offers stability and design flexibility for the residential marketplace and environmental advantages through every stage of manufacturing and use. Locally, the characteristic compressive strength is usually measured based on 150 mm cubes according to BS approach. But in future, the design compressive strength is usually based on the standard 150 x 300 mm cylinders as recommendation by Eurocode. Compression Test, Rebound Hammer Test and Ultrasonic Pulse Velocity Test method are used to determine the compressive strength. Each of the method gives the different method to measure compressive strength value. Experimental results indicate that the ratio of cylinder to cube samples was ranging between 0.70 and 0.83. It was found, that on average, the ratio of the compressive strength of 150 x 300 mm cylinders to 150 mm cubes was 0.79. Rebound Hammer method was preferable to be used for Non Destructive Test due to the slightly differences of compressive strength value compared to Ultrasonic Pulse Velocity method. A comparison of the compressive strength between Compression Test method on cube, Rebound Hammer method and Ultrasonic Pulse Velocity method on prism was performed. These types of methods were chosen because it represented Destructive and Non Destructive test that are most commonly used locally in the construction industry and research.